The anthropologist as curator - Sansi, Roger (Bloomsbury Academic, 2020)
"Why do contemporary art curators define their work as ethnography? How can curation illuminate the practice of contemporary anthropology? Does anthropology risk disappearing as a specific discipline within the general model of the curatorial? The Anthropologist as Curator collects together the research of international scholars working at the intersection of anthropology and contemporary art in order to explore these questions. The essays in the book challenge what it means to do ethnographic work, as well as the very definition of the discipline of anthropology in confrontation with the model of the curatorial. The contributors examine these ideas from a variety of angles, and the book includes perspectives from anthropologists who have set up their own exhibitions; those who have conducted fieldwork on the arts, including participatory practices, digital images and sound; and contributors who are currently working in a curatorial capacity at a museum. With case studies from the USA, Canada, Germany, Brazil, Mexico, India and Japan, the book represents an international perspective and is relevant to students and scholars of anthropology, contemporary art, museum studies, curatorial studies and heritage studies"--